Efficacy analysis of quadruple nerve decompression surgery for lower limb diabetic peripheral neuropathy - Zhang, Yong; Li, Zonghan; Ma, Tianyi; Xu, Xiaodong; Li, Jicheng; Dai, Rufei; Shen, Jiawei (Frontiers in Surgery, 2026)
ObjectiveTo explore the efficacy of quadruple nerve decompression in treating painful diabetic peripheral neuropathy (PDPN) of lower extremity, and to evaluate its clinical value in pain relief and sensory recovery.MethodA retrospective analysis was performed on 26 PDPN patients (45 sides), all of whom underwent quadruple nerve decompression, including release of the common peroneal nerve (CPN), superficial peroneal nerve (SPN), deep peroneal nerve (DPN), and tibial nerve (TN). Changes in the Visual Analog Scale (VAS) score, two-point discrimination (TPD), sensory nerve conduction velocity (SCV), and Toronto Clinical Scoring System (TCSS) score were evaluated by comparing preoperative values with those at an average of 30.46 months postoperatively. Statistical analysis was conducted using the paired t-test.ResultsPostoperative VAS scores were significantly reduced, from 7.31 ± 1.62 to 2.51 ± 1.47 (P < 0.001), with 93.3% of limbs achieving at least 50% pain relief. TPD showed significant improvement, decreasing from 13.80 ± 3.01 mm to 7.49 ± 2.07 mm (P < 0.001), and 68.9% of patients returned to normal levels. The proportion of nerves showing an SCV improvement of ≥5 m/s ranged from 64.4% to 75.6%. TCSS scores shifted from all being grade III before surgery to mild or moderate in 93.3% of cases. No severe complications were observed postoperatively.ConclusionSignificant pain relief and improvement in sensation and nerve function have been achieved in patients with PDPN through quadruple nerve decompression, which addresses multiple potential nerve entrapment sites. This procedure, building upon existing evidence, demonstrates sustained efficacy in pain relief and sensory recovery over a median 30-month follow-up, offering a refined surgical option for patients with refractory PDPN who have failed conservative management.